Bài 9: Phân tích đa thức thành nhân tử bằng cách phối hợp nhiều phương pháp

NL

PTĐTTNT

ab(a+b)-bc(b+c)+ac(a-c)+2abc

NL
30 tháng 10 2017 lúc 20:43

ab(a+b)-bc(b+c)+ac(a-c)+2abc = [ab(a+b)+abc]-[bc(b+c)+abc]+ac(a-c)

=ab(a+b+c)-bc(a+b+c)+ac(a-c)

=(ab-bc)(a+b+c)+ac(a-c)

=b(a-c)(a+b+c)+ac(a-c)

=(a-c)[b(a+b+c)+ac] = (a-c)(ab+bc+ac+b2)

Bình luận (0)
NL
30 tháng 10 2017 lúc 20:45

mk sửa thêm nha :

(a-c)(ab+bc+ac+b2) = (a-c)[(ab+ac)+(bc+b2)] = (a-c)[a(b+c)+b(b+c)]

= (a-c)(a+b)(b+c)

Bình luận (0)

Các câu hỏi tương tự
TM
Xem chi tiết
LN
Xem chi tiết
NN
Xem chi tiết
HA
Xem chi tiết
NM
Xem chi tiết
NM
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
QN
Xem chi tiết